Bone marrow in nine cases of clinical glandular fever and a review of the literature. Issue 6 (November 1968) - Boyd, J. F.; Reid, D.
Abstract : A review of the literature and the findings of a bone marrow examination in nine patients with glandular fever are reported. All marrows showed marked generalized hyperplasia of erythroid, myeloid, megakaryocytic, and reticulum cell elements with a greater or less `shift to the left' in the first three cell groups. The hyperplasia was maximal in two cases. Another case (the index case which was responsible for initiating this study) showed extremely bizarre cytological features of all four elements, and from many fields in the marrow smears it would have been possible to make a diagnosis of malignant transformation of any of the four marrow components. All these changes had returned to near normality on repeat marrow examination 15 months later.